ANALISIS IMPLEMENTASI KEBIJAKAN KETAHANAN KELUARGA ANTI NARKOBA PADA BADAN NARKOTIKA NASIONAL REPUBLIK INDONESIA - Eva Fitri Yuanita; Mala Sondang Silitonga; Hamka (Halu Oleo University, 2024)
The aim of this research is to analyze the implementation of the Anti-Drug Family Resilience Policy at the National Narcotics Board of the Republic of Indonesia. This research uses qualitative methods by conducting interviews, observation and documentation. The data source in this research uses secondary data and primary data. The informants in this research are policy makers in the field of prevention and prevention practitioners who implement family resilience programs with the BNN at both the central and district/city levels. According to the findings of the analysis, the anti-drug family resilience at BNN RI was the issue that was prioritized. This was done as an activity program that adapted evidence-based prevention that had been tested internationally. Therefore, it was very appropriate if this was supported by optimizing the anti-drug family resilience policy. The National Narcotics Board of the Republic of Indonesia's anti-drug family resilience policy isn't yet perfect. One of the reasons is that there is not any statutory or policy regulations issued by BNN as the leading sector in efforts to prevent drugs through strengthening families.